21st International Conference on Offshore Mechanics and Arctic Engineering, Volume 1 2002
DOI: 10.1115/omae2002-28126
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Stress Analysis of Complex Umbilical Cross-Sections

Abstract: Nexans Norway is, together with Marintek, currently developing a software for detailed analysis of complex umbilical cross-section designs. The software development project combines numerical methods with small-scale testing of involved materials, as well as full-scale testing of a wide variety of umbilical designs, essential for calibration and verification purposes. Each umbilical design is modelled and comparisons are made with respect to global behaviour in terms of: • Axial strain versus axial force; • Ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Numerical studies have been performed to analyze the bending behavior of the unbonded flexible pipes. Saevik and Ekeberg (2009) developed specialized software by combining the numerical method with model tests, material tests, and full-scale experiments to analyze stresses in the armor wire section based on curved beam and thin shell theory. Zhang and Qiu (2007) proposed a simple model to simulate the behavior of tensile armored steel wire during unbonded flexible pipe bending and analyzed the displacement field of the wire, stress-strain in the wire cross-section, armored wire extrusion with other layers, and bending hysteresis.…”
Section: Theoretical and Simulation Research Progress On Armor Layer ...mentioning
confidence: 99%
“…Numerical studies have been performed to analyze the bending behavior of the unbonded flexible pipes. Saevik and Ekeberg (2009) developed specialized software by combining the numerical method with model tests, material tests, and full-scale experiments to analyze stresses in the armor wire section based on curved beam and thin shell theory. Zhang and Qiu (2007) proposed a simple model to simulate the behavior of tensile armored steel wire during unbonded flexible pipe bending and analyzed the displacement field of the wire, stress-strain in the wire cross-section, armored wire extrusion with other layers, and bending hysteresis.…”
Section: Theoretical and Simulation Research Progress On Armor Layer ...mentioning
confidence: 99%
“…Hence, there are more uncertainties related to prediction of frictional stresses due to larger pitch length and the elastic energy stored in an element during bending, which has encouraged many researchers to develop methodologies to accurately calculate fatigue life of umbilicals by considering nonlinear effects and frictional stresses. Among these efforts are works by Witz and Tan [9], Saevik and Ekeberg [10], Sodahl et al [11], and Qing-zhen et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, static and dynamic friction coefficients and the corresponding smooth transition between these two friction coefficients were observed by Rabinowicz [8] in some tests. Several works have been reported in the literature, see [3,9,10,11,12,13], concerning the hysteric bending behavior of helix elements versus full scale tests. Most of the work demonstrated that good correlation in terms of axial stress of helix elements and hysteresis bending moment-curvature relationship.…”
Section: Introductionmentioning
confidence: 99%